Effects of functional alkali in magnetorheological finishing fluid. (21st December 2020) - Zhang, Yunfei; Fang, Fengzhou; Wang, Lili; Li, Xiaoyuan; Liu, Jiabao; Ye, Zuoyan; Tian, Dong; Huang, Wen; Yu, Miao; Ye, Minheng; Wang, Chao
Abstract: Magnetorheological (MR) fluids can be utilized for ultra-precise finishing, for instance, in fused silica (FS) optics in giant laser system. However, few modification methods of MR fluid can improve the material removal rate (MRR) and surface quality of the finished optics simultaneously. In this study, we investigated the application of functional alkali additives in MR finishing fluid. MRR was doubled over the untreated MR fluid; meanwhile the surface roughness of the FS converged to 0.44 nm. Such excellent finishing performance can be mainly attributed to the dual functional effects of the triethanol amine (TEA) alkali, the hydroxides released by TEA contributes to the MRR increase and the steric hindrance effect of the ethanol ligands helps improve the surface quality.